Composite Parts Assembly Operational Improvements. Issue 1 (20th February 2020) - Greco, Alessandro; Caputo, Francesco; Caterino, Mario; D'Ambra, Sara; Fera, Marcello; Laudante, Elena
Abstract: In the era of Industry 4.0, automation plays a key role in improving manufacturing production processes in terms of working times, accuracy of operations, products' quality, and so on. With focus on the working tasks on composite components, drilling and riveting operations require particular attention due to the possibility of damage to the final product, especially when they are executed manually. To reduce these kinds of risks, the introduction of a robot in the working area could represent an improvement to speed up the processes and to ensure a better quality result. It is worth noting that human intervention remains necessary for carrying out a part of the sub‐tasks, especially in the case of composite assembly procedures. This paper aims at presenting a case study about the drilling and riveting operations on a composite aircraft fuselage whose working cell is characterized by the coexistence of a human and a robot. Moreover, the implementation of a numerical simulation allows validating the working cycle and the adopted solutions in terms of ergonomic performance.